Changing Words of Absolution in Sacramental Confession: Canon 838 - Huels, John M. (Roman replies and CLSA advisory opinions 1997, 1997)
We were told that one of our priests had used the words, ''I release you from your sins, " in giving absolution during the sacrament of penance. Since the words of absolution are constitutive of the sacrament, would this change affect its validity?